2010
DOI: 10.3109/02688697.2010.508849
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cranio-spinal involvement of Rosai-Dorfman disease: case report

Abstract: Rosai-Dorfman disease is a rare non-neoplastic lymphoproliferative condition. It commonly affects individuals between third and fifth decades, most common presentation being in the form of massive painless cervical lymphadenopathy with fever, weight loss and malaise. Isolated intracranial involvement is rare seen in less than 5% of patients with extranodal involvement. We present a patient with isolated contiguous cranio-spinal involvement who presented to us with remitting symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…[9] A review of the literature showed that to date there are about 50 reported cases of isolated extranodal CNS RDD described in 6 other articles. [13810131618] Most cases have a florid presentation with seizures or headaches and neurological deficits like visual loss and limb weakness or numbness being most common.…”
Section: Discussionmentioning
confidence: 99%
“…[9] A review of the literature showed that to date there are about 50 reported cases of isolated extranodal CNS RDD described in 6 other articles. [13810131618] Most cases have a florid presentation with seizures or headaches and neurological deficits like visual loss and limb weakness or numbness being most common.…”
Section: Discussionmentioning
confidence: 99%
“…After injection of gadolinium contrast agent, the lesion shows homogeneously or inhomogeneously intense enhancement, and the dural tail sign can often be found. [4,11] In our present case, brain MRI revealed a well-defined homogenous mass which is closely related to the dura mater in the foramen magnum extending toward the cervical spinal canal; the lesion was isointense on T1WI, hypointense on T2WI, and intensely enhanced with gadolinium. These above radiological findings are difficult to preoperatively distinguish RDD from meningioma.…”
Section: Discussionmentioning
confidence: 47%
“…CNS involvement is rare in RDD, and it usually presents in the form of a well-defined, solitary, extraparenchymal supratentorial dura-based lesion resembling a meningioma in neuroimaging scans. 3 Lesions located in the posterior fossa and extending to the cervical spinal canal, as in our case, are rare.…”
mentioning
confidence: 54%
“…To the best of our knowledge, only three cases of RDD displaying spinal cord compression secondary to craniocervical junction involvement have been reported since the disease was first described in 1969. 2 3 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation